Existential Development of Jason Dessen in Blake Crouch’s Dark Matter: A Kierkegaardian Perspective - Arditya Rizky Pradana; Ida Puspita; Nur Rifai Akhsan (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2025)
This article examines the existential development of Jason Dessen, the protagonist of Blake Crouch’s Dark Matter (2016), through Søren Kierkegaard’s theory of the three stages of existence: the aesthetic, the ethical, and the religious. Drawing on close textual analysis, the study demonstrates that Jason initially inhabits an aesthetic mode of existence marked by dissatisfaction, existential anxiety, and an illusory pursuit of freedom grounded in unrealized possibility. His trajectory then moves toward ethical existence, in which responsibility, commitment, and moral accountability, particularly in relation to family, become central to his sense of selfhood and meaning. Jason’s journey ultimately culminates in a form of religious existence, articulated in a contemporary, non-theistic mode, characterized by surrender, sacrifice, and a leap of faith that transcends rational calculation and ethical certainty. By mapping Jason’s inward transformation onto Kierkegaard’s existential stages, this study highlights the philosophical depth of Dark Matter and extends existing interpretations beyond scientific or rational-choice frameworks. The article concludes that Dark Matter recontextualizes Kierkegaardian existentialism within modern science fiction, demonstrating the continued relevance of existential philosophy for negotiating contemporary anxieties surrounding identity, freedom, choice, and the search for meaning under conditions of radical uncertainty.